(untitled) (Biological Sciences - PJSIR, 2010)
. In the assessment of variation trends in ambient air quality at five selected regions of Karachi city, four air pollutants namely carbon monoxide, sulphur dioxide, nitrogen oxide and nitrogen dioxide were monitored, along with metrological parameters, for eight consecutive days. The results suggested that all the pollutants were mainly due to the emissions from motor vehicles and industries, owing to the absence of regulatory laws/standards about ambient air quality in Pakistan. The results have been discussed with reference to recommendations of the World Health Organiza- tion for the same.